The Meaning of Defending the Country as Strengthening Non-Military Security: Perceptions of Indonesian Society - Ridwan; Yoga S, Windhiadi; Krisnando N, Garcia; Nidatya, Nurfarah (Penerbit STKIP PGRI Bangkalan, 2023)
Shifting threats regarding state sovereignty and resilience are currently experiencing a shift. In addition to military threats, non-military threats are also threats that are no less important for the sustainability of a country. Public perception of threats and their relation to defending the state is essential because protecting the state is not only the obligation of the TNI and Polri but all Indonesian citizens. This study aims to explain the meaning of defending the country as Non-Military Security Strengthening and its relation to public perceptions of current threats. The research method used in this research is a qualitative descriptive research method. The results of this study indicate that public perceptions of threats ranging from non-military threats such as the Covid-19 pandemic, diminishing job opportunities, unequal education, corruption of political elites, The erosion of national culture by foreign influences, natural disasters (floods, landslides, earthquake, volcanic eruptions, etc.), the potential for social conflict due to poor tolerance between religious communities, the rise of hoaxes, and hate speech in cyberspace/the internet for the increase of crime and the spread of drugs. As for the strategy to deal with non-military threats, non-physical State Defense can overcome them. According to the threat perception, the process can be carried out through dedication according to their respective professions and strengthening the values of defending the country, such as love for the motherland, awareness of the nation and state, loyalty to Pancasila, willingness to sacrifice for the nation, as well as the initial ability to defend the country.